Plasma androgen receptor and response to adapted and standard docetaxel regimen in castration-resistant prostate cancer: A multicenter biomarker study. (July 2021) - Conteduca, Vincenza; Wetterskog, Daniel; Castro, Elena; Scarpi, Emanuela; Romero-Laorden, Nuria; Gurioli, Giorgia; Jayaram, Anuradha; Lolli, Cristian; Schepisi, Giuseppe; Wingate, Anna; Casadei, Chiara; Lozano, Rebeca; et al.
Abstract: Background: Plasma AR status has been identified as a potential biomarker of response in metastatic castration-resistant prostate cancer (mCRPC) patients receiving docetaxel or AR-targeted therapies. However, the relevance of plasma AR in the overall management of CRPC patients receiving different docetaxel doses is unknown. Patients and methods: This was a multi-institution study of associations between baseline plasma AR copy number status, assessed by droplet digital PCR, and outcome in 325 mCRPC patients receiving docetaxel at standard or adapted regimen at the discretion of the treating physician. Upon analysis, patients were assigned randomly to either a training (n = 217) or validation (n = 108) cohort. Results: In the training cohort, AR -gained patients treated with adapted docetaxel regimen had a significantly worse median progression-free survival (PFS) (3.8 vs 6.3 months, hazard ratio [HR] 2.58, 95% confidence interval [CI] 1.34–4.95, p < 0.0001), median overall survival (10.8 vs 20.6 months, HR 1.98, 95% CI 1.09–3.62, p = 0.0064) and PSA response (PSA > −50%: odds ratio 4.88 95%CI 1.55–14.32, p = 0.013) as compared to plasma AR normal patients. These findings were all confirmed in the validation cohort. However, in patients treated with standard docetaxel regimen, these differences were not seen. The interaction between AR CN status and dose reduction of docetaxel was considered as independent factor for PFS in both the training and validation cohort (HR 2.84, 95% CI 1.41–5.73, p = 0.003, and HR 4.79, 95% CI 1.79–12.82, p = 0.002). Conclusion: Despite the retrospective non-randomised design of this study, our hypothesis-generating findings could suggest plasma AR as a potential biomarker for optimal docetaxel timing and dose in mCRPC patients. Prospective trials are warranted. Highlights: Plasma  AR  may help in choosing between adapted and standard docetaxel dose in mCRPC. Molecular evidence aid to select the proper timing and dose of docetaxel. Prospective trials to validate these findings are warranted.